DAYA DUKUNG DAN DAYA TAMPUNG WISATAWAN SITUS PERAHU KUNO DESA PUJULHARJO KECAMATAN REMBANG KABUPATEN REMBANG - Putra, Kiswanto Syah; Syah Putra, Rizal Rizal Ichsan (Jounal of Enviromental Science Sustainable, 2023)
In the tourism sector, the concepts of carrying capacity and carrying capacity have a significant role in maintaining a balance between economic growth and environmental preservation. Carrying capacity refers to the capability of a tourist destination or tourism area to manage the number of visitors without disturbing the natural ecosystem, cultural heritage and local social dynamics. Conversely, capacity describes the maximum number of tourists that can be received by a destination without reducing the quality of the tourist experience or disrupting the balance of ecosystems and local community interactions. An analysis of carrying capacity and carrying capacity in the context of tourism includes measuring and assessing the various factors that influence the relationship between visitors, the environment and the local community. These factors include accommodation infrastructure, means of transportation, waste management, water sources, as well as social dimensions such as local customs and cultural values. The main aim of this analysis is to avoid "over-tourism," where an increase in the number of visitors exceeds the carrying capacity and carrying capacity of a destination, which has the potential to cause environmental damage, disputes with local residents, and a decrease in the quality of the visitor experience. Such analysis supports governments, tourism companies and local communities in designing sustainable management plans and advancing a vision for the future. With an integral and sustainable approach to the concepts of carrying capacity and carrying capacity, tourism destinations can optimize their economic impact while minimizing negative effects on the environment and cultural identity. By considering environmental and social aspects, and involving all interested parties, the analysis of carrying capacity and capacity provides a strong foundation for responsible and sustainable tourism development